The Role Of Adab Evaluation Sheets In Improving Students' Spiritual Attitudes In Islamic Religious Education Subjects - Gita Dyah Azzarah Titis Parmitha; Dzulfikar Akbar Romadlon (At-Tarbiyat, 2024)
This research aims to determine the role of the adab evaluation sheet media in PAI learning subjects on students' spiritual attitudes, which is based on a state elementary school located on the outskirts of the city. The results of the researcher's observations concluded that in the initial observation, the researcher found that students did not understand and practice good character in everyday life, such as respect for older people, which was identified through when they spoke to older people, behavior when they meet on the street, and interrupt the conversation of older people when they are explaining learning or giving advice. This research uses a qualitative descriptive method which will explain the steps from distributing the etiquette evaluation sheets to the results. The final results of the assessment of the adab evaluation sheet are very influential in improving students' spiritual attitudes of adab where the percentage scale reaches 7.63%. In this way, the etiquette evaluation sheet becomes a form of daily monitoring that can be used to control students' etiquette so that they continue to carry out the noble etiquette that has been taught.